(untitled) (The Pretoria Student Law Review, 2021)
This paper will focus on the meaning of ‘advantage to creditors’ in the context of both voluntary and compulsory sequestration. The consequences of this requirement and the efficacy of the alternative debt relief measures to the Insolvency Act (the Act) will also be discussed. Recommendations to remedy the situation as it stands in South Africa will be submitted, taking into account all the proposed changes to South African insolvency law.